1984
DOI: 10.1093/cvr/18.7.443
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin content in human skeletal muscle and myocardium: relation to fibre size and oxidative capacity

Abstract: Myoglobin, muscle fibre diameter, and citrate synthase activity were measured in leg muscle of untrained and trained men and in the myocardium from the apex of the left ventricle and from papillary muscle in patients subjected to open heart surgery. The citrate synthase (CS) activity was 60% higher in trained than in untrained skeletal muscle. In the myocardium it was around four times greater than in untrained skeletal muscle but there was no difference between the apex of the left ventricle and papillary mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Table 1 (15). Similarly, the values for myoglobin (Mb) intermuscular concentration, [Mb], fell within a range of concentrations (0.26-0.52 mM) in tissue biopsies taken from adult quadriceps muscles (16)(17)(18). Most of the age-related differences were either not significant or small (Ͻ15%).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Table 1 (15). Similarly, the values for myoglobin (Mb) intermuscular concentration, [Mb], fell within a range of concentrations (0.26-0.52 mM) in tissue biopsies taken from adult quadriceps muscles (16)(17)(18). Most of the age-related differences were either not significant or small (Ͻ15%).…”
Section: Resultsmentioning
confidence: 75%
“…Resting muscle metabolism is measured to avoid the confounding effects of energetic differences between fiber types during exercise to permit focusing on mitochondrial energetics and the impact of uncoupling on cellular aging. [Mb], fell within a range of concentrations (0.26-0.52 mM) in tissue biopsies taken from adult quadriceps muscles (16)(17)(18). Most of the age-related differences were either not significant or small (Ͻ15%).…”
mentioning
confidence: 97%
“…The H-FABP content in cardiac muscle is higher than that in skeletal muscle, whereas the myoglobin content in cardiac muscle is lower than that in skeletal muscle. 7,11 Therefore, there is a sharp contrast in the content of each protein in the heart and skeletal muscle. The molecular weight of H-FABP is 15 kDa and that of myoglobin is 18 kDa, therefore it is expected that the sieving effect of hemodialysis dialysers on H-FABP and myoglobin would be similar because these proteins have almost the same molecular weights.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Comparative studies for the diagnosing of AMI have demonstrated that quantitative measurement of H-FABP is more sensitive than both myoglobin and CK-MB measurements, and more specific than myoglobin. 14,15 Clinical investigations of the release kinetics of H-FABP and other biochemical markers have revealed that H-FABP is elevated above the cut-off level within 3 h of onset, reaching a peak value at 4 h, and its release into the blood is approximately 24-36 h after onset of AMI.…”
Section: H-fabp Quantitative Assay and Rapid Panel Testmentioning
confidence: 99%